A Taxonomic Revision of Macropsychanthus (Leguminosae—Papilionoideae) Reveals New Species and New Circumscriptions in Southeast Asia and Oceania - Fonseca-Cortés, Andrés; Clark, Ruth P.; Snak, Cristiane; Queiroz, Luciano Paganucci De (Phytotaxa, 2025)
Macropsychanthus currently comprises 52 species, with Southeast Asia and Oceania ranking as the second-richest region in terms of species and where the genus exhibits the greatest diversity in floral structures. Until now, seven species have been recognized in this region, including M. lauterbachii, a taxon encompassing substantial morphological variation and previously divided into four varieties. As part of our revision of Macropsychanthus, we examined all species occurring in Southeast Asia and Oceania. Based on our findings, we propose M. javanicus as a synonym of M. hexander, and M. dolichobotrys and M. lauterbachii var. parviflorus as synonyms of M. carolinensis. We also elevate the remaining varieties of M. lauterbachii to species rank. In addition, we describe three new species: M. magnificus, M. bracteosus, and M. wiakabumba. With these changes, the number of recognized species in Southeast Asia and Oceania increases to 12.